NTMS-derived DTI-based motor fiber tracking in radiotherapy treatment planning of high-grade gliomas for avoidance of motor structures. (June 2022) - Diehl, Christian D.; Rosenkranz, Enrike; Mißlbeck, Martin; Schwendner, Maximilian; Sollmann, Nico; Ille, Sebastian; Meyer, Bernhard; Combs, Stephanie E.; Bernhardt, Denise; Krieg, Sandro M.
Highlights: nTMS (DTI-FTTMS detects cortical and subcortical motor areas. nTMS (DTI-FTTMS ) detects cortical and subcortical motor areas. DTI-FTTMS  can be easily implemented in RT planning of motor-eloquent glioma. With DTI-FTTMS the corticospinal tract can be spared without affecting PTV dose. Our approach might help to avoid neurological sequelae after RT. Abstract: Background: Management of high-grade gliomas (HGGs) close to motor areas is challenging due to the risk of treatment-related morbidity. Thus, for resection, functional mapping of the corticospinal tract (CST) with navigated transcranial magnetic stimulation (nTMS) combined with diffusion tensor imaging (DTI)-based fiber tracking (DTI-FTTMS ) is increasingly used. This study investigated the application of DTI-FTTMS in adjuvant radiation therapy (RT) planning of HGGs for CST avoidance. Methods: The preoperative DTI-FTTMS -based CST reconstructions of 35 patients harboring HGGs were incorporated into the RT planning system and merged with planning imaging. The CST was delineated as the planning risk volume (PRV-FTTMS ). Intensity-modulated RT (IMRT) plans were optimized to preserve PRV-FTTMS . Segments within the planning target volume (PTV) were not spared (overlap). Results: With plan optimization, mean dose (Dmean) of PRV-FTTMS can be reduced by 17.1% on average (range 0.1–37.9%), thus from 25.5 Gy to 21.2 Gy ( p  < 0.001). For PRV-FTTMS segments beyond the PTV dose, reduction is possible by 26.8% (range 0.1–43.9%, Dmean 17.4 Gy vs. 12.5 Gy, p  < 0.001). Considering only portions within the 50% isodose level, Dmean is decreased by 46.7% from 38.6 Gy to 20.5 Gy (range 19.1–62.8%, p  < 0.001). PTV coverage was not affected: V95% and V90% were 96.4 ± 3.1% and 98.0 ± 3.9% vs. 96.1 ± 3.5% ( p  = 0.34) and 98.3 ± 2.9% ( p  = 0.58). Dose constraints for organs at risk (OARs) were all met. Conclusion: This study demonstrates that DTI-FTTMS can be utilized in the RT planning of HGGs for CST sparing. However, the degree of dose reduction depends on the overlap with the PTV. The functional benefit needs to be investigated in future prospective clinical trials.